Weighted Composition Operators from Derivative Hardy Spaces into n-th Weighted-Type Spaces - Nanhui Hu (Journal of Mathematics)
The boundedness, compactness, and the essential norm of weighted composition operators from derivative Hardy spaces into n-th weighted-type spaces are investigated in this paper.